Reduction of drive for thinness and body dissatisfaction in people with self-reported dysregulated eating behaviors after intermittent theta burst stimulation (iTBS) of the left dorsolateral prefrontal cortex - Barone, Jennifer; Oliveri, Massimiliamo; Bonaventura, Rosario Emanuele; Mangano, Giuseppa Renata (Frontiers in Human Neuroscience, 2023)
Aim: This study aims to explore the effect of intermittent theta burst stimulation (iTBS) of the right and left dorsolateral prefrontal cortex (DLPFC) in people with self-reported dysregulated eating behaviors but without a diagnosis of eating disorders (ED). Methods: Participants were randomly divided into two equivalent groups according to the side (right or left) of the hemisphere to be stimulated and they were tested before and after a single iTBS session. Outcome measurements were scores on self-report questionnaires assessing psychological dimensions related to eating behaviors (EDI-3), anxiety (STAI-Y), and tonic electrodermal activity. Results: The iTBS interfered with both psychological and neurophysiological measures. Significantly variations of physiological arousal after iTBS of both the right and left DLPFC were witnessed by increased mean amplitude of non specific skin conductance responses. As concerns to the psychological measures, the iTBS on the left DLPFC significantly reduced the scores of the EDI-3 subscales Drive for thinness and Body dissatisfaction. Interestingly, these two scales are two of the three (Drive for thinness, Body dissatisfaction, and Bulimia) EDI-3 clinic scales used as specific markers to assess the onset and/or maintenance of eating disorders. Conclusion: Our results show an impact of the left DLPFC iTBS on the psychological dimensions that represent risk factors for the onset of eating disorders suggesting that an altered hemispheric asymmetry similar to that encountered in clinical populations, is present in normal subjects even if in the absence of clinical symptoms.